Curent Situation of “Candidatus Liberibacter asiaticus” in Guangdong, China, Where Citrus Huanglongbing Was First Described - Xiao-ling DENG; Yi-di GAO; Jian-chi CHEN; Xue-lian PU; Wei-wen KONG; Hua-ping LI (Journal of Integrative Agriculture, 2012)
Citrus Huanglongbing (HLB, yellow shoot disease) was first observed in the coastal Chaoshan Plain of Guangdong Province, China, in the late 19th century based on descriptions of yellow shoot symptoms. “Candidatus Liberibacter asiaticus” has been considered as a putative pathogen associated with HLB since 1994. Information about the curent prevalence of this bacterium is important for HLB control in Guangdong and also provides useful reference for HLB study elsewhere. In 2007, we collected HLB symptomatic citrus samples from 16 cultivars in 12 prefecture cities, mostly in the north and west regions of Guangdong, where major citrus fruits are currently produced. Among the 359 samples collected, 241 (67.1%) were positive for “Ca. L. asiaticus”, distributed in 15 out of the 16 cultivars from all 12 cities, indicating the widespread prevalence of “Ca. L. asiaticus” in Guangdong Province. The detection rates varied from 16.7 to 100% depending on location and cultivar. Lower detection rates were found in newer citrus cultivation cities among the previously less popular but now promoted cultivars. In reviewing the citrus management and pest control practice, we believe that infected nursery stocks play a key role in the current spread of “Ca. L. asiaticus”.